2015
DOI: 10.1073/pnas.1506279112
|View full text |Cite
|
Sign up to set email alerts
|

Biodiversity inhibits parasites: Broad evidence for the dilution effect

Abstract: Infectious diseases of humans, wildlife, and domesticated species are increasing worldwide, driving the need to understand the mechanisms that shape outbreaks. Simultaneously, human activities are drastically reducing biodiversity. These concurrent patterns have prompted repeated suggestions that biodiversity and disease are linked. For example, the dilution effect hypothesis posits that these patterns are causally related; diverse host communities inhibit the spread of parasites via several mechanisms, such a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

15
542
5
6

Year Published

2016
2016
2023
2023

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 580 publications
(595 citation statements)
references
References 34 publications
15
542
5
6
Order By: Relevance
“…The third pathogen, the chytrid fungus Batrachochytrium dendrobatidis (Bd), is considered one of the deadliest organisms on the planet because of its association with hundreds of amphibian extinctions in the last half century (21,22). We chose to model the spatial factors affecting these pathogens because (i) spatially explicit datasets of their distributions were available (but were not available for other pathogens or other organisms in general; see Methods); (ii) they span a diversity of taxa (a virus, bacterium, and fungus) and transmission modes (WNV and Lyme are mosquito-and tick-borne, respectively, and Bd is a directly transmitted, water-borne pathogen), and infect various types of hosts (endothermic and ectothermic), increasing the generality of our findings; (iii) they are widespread generalists throughout the United States, providing a spatial extent great enough to conduct largescale analyses; (iv) their abundances or prevalences appear to be partially controlled by a common biotic factor, the richness of potential hosts (19,21,23,24), and by common abiotic factors, including climate and vegetation (20,25,26); and, finally, (v) understanding emerging diseases is of critical importance to biodiversity conservation and human health. Our goal was not to develop and put forth the best possible model to explain the spread of these diseases but rather to test whether spatial scale influences which types of ecological processes are important.…”
Section: Significancementioning
confidence: 80%
See 1 more Smart Citation
“…The third pathogen, the chytrid fungus Batrachochytrium dendrobatidis (Bd), is considered one of the deadliest organisms on the planet because of its association with hundreds of amphibian extinctions in the last half century (21,22). We chose to model the spatial factors affecting these pathogens because (i) spatially explicit datasets of their distributions were available (but were not available for other pathogens or other organisms in general; see Methods); (ii) they span a diversity of taxa (a virus, bacterium, and fungus) and transmission modes (WNV and Lyme are mosquito-and tick-borne, respectively, and Bd is a directly transmitted, water-borne pathogen), and infect various types of hosts (endothermic and ectothermic), increasing the generality of our findings; (iii) they are widespread generalists throughout the United States, providing a spatial extent great enough to conduct largescale analyses; (iv) their abundances or prevalences appear to be partially controlled by a common biotic factor, the richness of potential hosts (19,21,23,24), and by common abiotic factors, including climate and vegetation (20,25,26); and, finally, (v) understanding emerging diseases is of critical importance to biodiversity conservation and human health. Our goal was not to develop and put forth the best possible model to explain the spread of these diseases but rather to test whether spatial scale influences which types of ecological processes are important.…”
Section: Significancementioning
confidence: 80%
“…Because the abundance of all three pathogens has been shown previously to be affected by a common biotic factor, the richness of potential hosts (defined as the richness of all species that receive either successful or failed transmission attempts from a generalist pathogen or vector) (19,21,23,24), we chose to use this factor in our models to represent the subset of biotic interactions that drive the processes causing dilution or amplification effects (5). We used total amphibian richness to predict the spread of Bd, avian richness for WNV, and mammalian richness for Lyme disease (we also initially tested the richness of other taxa for B. burgdorferi; see Methods).…”
Section: Significancementioning
confidence: 99%
“…These biodiversity-ecosystem functioning (BEF) studies have revealed generally positive effects of species richness on primary productivity and also shed light on the mechanisms that promote productivity under these conditions (3). Niche differentiation among species can enhance community-level productivity through complementary resource use, decreased competition (3), and reduced density-dependent herbivore and pathogen pressure (4). Facilitation can increase community-level productivity via positive effects of one species on another.…”
mentioning
confidence: 99%
“…However, systems might not always meet these conditions, which has sparked an intense debate over the generality of the dilution effect of host species richness 158,270,271 . A recent meta-analysis concluded that the majority of studies showed a decrease of pathogen prevalence with increasing species richness 251 . Of course this is good news for conservationists trying to convince governments to preserve biodiversity.…”
Section: The Idiosyncratic Link Between Biodiversity and Tick-borne Dmentioning
confidence: 99%
“…For tick-borne pathogens vectored by a generalist species, the main conditions for a dilution effect to occur are that 1) pathogen prevalence increases with the density of host species with the highest reservoir competence and that 2) the density of these host species decreases with host species richness 3 . It has been shown that a dilution effect of host species richness occurs in many disease systems 251 , including the Lyme borreliosis system in North America, where a dilution effect of host species richness was found both at a small 230 and a large spatial scale 248 . However, the mechanisms underlying any negative correlation with host species richness remain relatively unstudied 218 .…”
Section: Introductionmentioning
confidence: 99%